ALKHAIRAAT DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI BOALEMO - Siti Arafah (EDUCANDUM, 2017)
This study aims to describe the development of Islamic education by Alkhairaat inBoalemo. This type of research is qualitative by using data collection method throughobservation, documentation and wawacnara. The results showed that the presence ofAlkhairaat in Boalemo (Tilamuta) in 1967 was the forerunner of the growth anddevelopment of Alkhairaat in Gorontalo. Alkhairaat from time to time continue toexperience development and improvement, starting from the beginning to the currentperiod, pioneering education starting from kindergarten / TPA to college. Developmentof education Alkhairaat in Boalemo in five sub-districts in Boalemo where educationalinstitutions vary from TK-MA. The presence of Alkhiraat as the organizer of Islamicreligious education, has been responded positively by the society, and became thefoundation for the society and considered to be able to answer the educational needsof the young generation in particular and the fulfillment of religious needs for thecommon people.